RANCANG BANGUN IDENTIFIKASI KEBUTUHAN KALORI DENGAN APLIKASI GO HEALTHY LIFE - rusliyawati rusliyawati; Anggun Dwi Suryani; Qadhli Jafar Ardian (Jurnal Teknologi dan Sistem Informasi, 2020)
Nutrition is the organic substances needed by the organism for the normal functioning of the body system, growth, health maintenance. The availability of a variety of fast food and prepared foods, and ignorance about nutrition, causes this age group to tend to be mildly active, which results in one of which is unbalanced and unhygienic food consumption. Therefore, attention to balanced nutrition behavior needs to be increased to achieve a healthy, active and productive lifestyle. In the current era, Bandarlampung people, especially in adults, experience a lot of bodies that are not ideal due to inappropriate body weight, between excess weight (fat) compared to height or between underweight (thin) compared to height. Lack of community knowledge about nutrition, also affects the health of their bodies. One way to identify nutritional needs in a person is with qualitative and quantitative data to make it easier to see and provide information related to support in calorie needs, namely by using the Go Healthy Life application, with the aim that people can easily and quickly find out their nutritional information. from nutritional status, ideal body weight, ideal height, number of calorie needs, activities undertaken, planning a diet based on the number of calorie needs and being able to communicate with nutritionists about nutrition without having to meet face to face. The results of this study can determine the composition of the diet menu in accordance with the number of calorie needs needed by patients with an accuracy of 100%.